O custo da maternidade: entre a profissão de comissária de vôo e a responsabilidade doméstica - Barbara Maria de Lana Luiz (2019)
This study focuses on the demonstration and understanding of the gender inequalities that still persist currently and is illustrated, among other forms, through conciliation of tasks by women who demonstrate that although in the labor market are still responsible for the household chores and motherhood. Seen in these terms, the purpose of this research is to identify and study the manners adopted by women to conciliate professional career and maternity, tracing the conditions for conciling tasks experienced by women, mothers, flight attendants, and belonging to the middle class, in order to understand this dynamic, within the perspective of the gender inequalities that, today, still exist. Focusing on this purpose, a qualitative research was conducted through semi-directive interviews in order to understand condition of conciliation of these women through their story from childhood to the current days.